MODEL IMPLEMENTASI KNOWLEDGE MANAGEMENT DALAM MENCIPTAKAN INOVASI PADA INDUSTRI KREATIF DI KOTA BANDUNG - Sri Suwarsi (Universitas Islam Bandung, 2016)
Friction from economic based industry paradigm to knowledge and information based industry paradigm require knowledge management. Nowadays, an organization is not only depend on resource based competitive advantage but also how it can compete with its own knowledge based, with a good knowledge management, organization can create knowledge workers so it can create the creative and innovative output, because it has supported by the employee’s competencies. In Bandung City, creative industry is very potential from the perspective of quantity and quality, but in the growth of the industry, there isi still no system and deep discussion about what is the talent of Bandung for being further explore until it can outcome core competencies for us to rely